Kinetics and mechanism of mechanochemical synthesis of hafnium nitride ceramics in a planetary ball mill. Issue 18 (15th December 2019) - Nepapushev, A.A.; Buinevich, V.S.; Gallington, L.C.; Pauls, J.M.; Orlova, T.; Miloserdova, O.M.; Chapysheva, N.V.; Rogachev, A.S.; Mukasyan, A.S.
Abstract: Mechanochemical synthesis of hafnium nitride ceramic powder was accomplished through direct nitridation of hafnium particles in nitrogen atmosphere during high-energy milling in a planetary ball mill. The nitrogen content was measured and evaluated to determine the reaction kinetics for hafnium – nitrogen across a range of treatment durations. The observed reaction rates are notably faster than for conventional thermal treatment, and, for hafnium treated for 5 min in the ball mill, the onset of nitridation begins at a temperature 200 °C lower than for the initial hafnium metal. The crystal structure and microstructure transformations were also investigated. A mechanism for the rapid hafnium nitridation occurring under high-energy ball milling conditions is proposed and discussed. Based on this proposed mechanism of metal nitridation via ball mill treatment in nitrogen atmosphere, we may suggest this process as an effective method for fabrication of fine (sub-micron) hafnium nitride powder from relatively large (10–100 μm) initial metal particles.